2009
DOI: 10.1038/emboj.2009.196
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles for A-type lamins in telomere biology and the DNA damage response pathway

Abstract: A-type lamins are intermediate filament proteins that provide a scaffold for protein complexes regulating nuclear structure and function. Mutations in the LMNA gene are linked to a variety of degenerative disorders termed laminopathies, whereas changes in the expression of lamins are associated with tumourigenesis. The molecular pathways affected by alterations of A-type lamins and how they contribute to disease are poorly understood. Here, we show that A-type lamins have a key role in the maintenance of telom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
256
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 213 publications
(273 citation statements)
references
References 71 publications
14
256
3
Order By: Relevance
“…Telomere function requires a normal nuclear lamina and dysfunctional, shortened telomeres have been observed in HGPS and lamin A-deficient cells (Taimen et al, 2009;Gonzalez-Suarez et al, 2009;Decker et al, 2009). Our data showed that only lamin mutant cells expressed detectable levels of PIN2/ TRF-1 telomerase inhibitor, whose overexpression leads to shortened telomeres (Zhou et al, 2003).…”
Section: High Throughput Proteomic Analysissupporting
confidence: 51%
“…Telomere function requires a normal nuclear lamina and dysfunctional, shortened telomeres have been observed in HGPS and lamin A-deficient cells (Taimen et al, 2009;Gonzalez-Suarez et al, 2009;Decker et al, 2009). Our data showed that only lamin mutant cells expressed detectable levels of PIN2/ TRF-1 telomerase inhibitor, whose overexpression leads to shortened telomeres (Zhou et al, 2003).…”
Section: High Throughput Proteomic Analysissupporting
confidence: 51%
“…In addition, we found that loss of A-type lamins leads to decreased levels of 53BP1, due to destabilization of the protein. 45 The decrease in 53BP1 levels is likely to be responsible for the low efficiency of end-to-end fusions upon telomere dysfunction in A-type lamins-deficient H4K20me3. Future experiments need to determine if ALT is the mechanism activated upon loss of Rb family members, and if A-type lamins inhibit recombination at telomeres.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in our laboratory has shown that A-type lamins bind to mouse telomeres and participate in their nuclear compartmentalization. 45 Embryonic fibroblasts from LMNA null mice exhibit changes in the nuclear distribution of telomeres towards the nuclear periphery and away from the nuclear center. This result was unexpected, since lamins are highly enriched at the nuclear periphery.…”
Section: A-type Lamins and Telomere Structure Length And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms sustaining this particular distribution of mammalian telomeres has never been studied in details and the only data that could be relevant for such a question are the demonstrations of telomeres association to nuclear matrix components, 10,11 transient association with mobile proteins of the Inner Nuclear Membrane (INM) at the end of mitosis 12 and functional relationship between telomere length or homeostasis and lamin A variants. 13 Recent evidence suggests that peripheral positioning and late replication might be concomitant (Arnoult et al, submitted) and that peripheral clustering of telomeres is a hallmark of senescence in human stem cells. 14 involved in enhancer-blocking activity, 7,8 both CTCF and A-type lamins mediate the D4Z4 insulator boundary activity against position effect.…”
Section: Extra Viewmentioning
confidence: 99%